The vehicle fleet and its relationship with respiratory diseases in Chiclayo, 2024 - Josué, Herrera Encalada,; Deslit, Jara Ayala, Ani; Paolo, Matos Manayay, Enrrique; Smith, Vásquez Flores, Anderson; Margot, Segura Saldarriaga, Adriana (Edelweiss Applied Science and Technology, 2025)
The main objective of this research is to analyze the relationship between the vehicle fleet of Chiclayo and the incidence of respiratory diseases in its population in order to propose solutions that improve air quality and, consequently, public health. The methodological approach used is quantitative-descriptive. The sample included 20 residents of the city, aged between 18 and 60 years. Data were obtained through a structured questionnaire consisting of 30 closed-ended questions, using a Likert scale from 1 to 5, and were classified into levels of environmental impact perception. The results indicate a significant correlation between the increase in the vehicle fleet and the prevalence of respiratory diseases, especially in the most trafficked areas. The conclusions suggest the need to implement strict environmental policies and promote the use of eco-friendly transportation to mitigate the negative effects on the respiratory health of the population.